Secondary histiocytic sarcoma may cause apparent persistence or recurrence of minimal residual disease in childhood acute lymphoblastic leukemia. Issue 9 (1st April 2015) - Alten, Julia; Klapper, Wolfram; Leuschner, Ivo; Eckert, Cornelia; Beier, Rita; Vallo, Elisabeth; Krause, Martin; Claviez, Alexander; Vieth, Simon; Bleckmann, Kirsten; Möricke, Anja; Schrappe, Martin; et al.
<x xml:space="preserve">Abstract</x> Histiocytic sarcoma (HS) is a rare disease with poor prognosis which may develop subsequent to acute lymphoblastic leukemia (ALL). Here we report two children treated within the AIEOP‐BFM ALL 2009 trial: one patient succumbed to fulminant hemophagocytic lymphohistiocytosis triggered by HS during ALL maintenance therapy, the other patient had a smoldering course of HS for over 2 years, and subsequently died after allogeneic stem cell transplantation. In both cases, HS and ALL were clonally related and apparent return of minimal residual disease (MRD) was detected by qPCR in bone marrow. Thus, HS should be considered in ALL when MRD appears to persist or reappear. Pediatr Blood Cancer 2015;62:1656–1660. © 2015 Wiley Periodicals, Inc.